Insights into flavor and key influencing factors of Maillard reaction products: A recent update - Liu, Shuyun; Sun, Hanju; Ma, Gang; Zhang, Tao; Wang, Lei; Pei, Hui; Li, Xiao; Gao, Lingyan (Frontiers in Nutrition, 2022)
During the food processing, especially heating, the flavor and color of food change to a great extent due to Maillard reaction (MR). MR is a natural process for improving the flavor in various model systems and food products. Maillard reaction Products (MRPs) serve as ideal materials for the production of diverse flavors, which ultimately improve the flavor or reduce the odor of raw materials. Due to the complexity of the reaction, MR is affected by various factors, such as protein source, hydrolysis conditions, polypeptide molecular weight, temperature, and pH. In the recent years, much emphasis is given on conditional MR that could be used in production of flavor-enhancing peptides and other compounds to increase the consumer preference and acceptability of processed foods. Recent reviews have highlighted the effects MR on the functional and biological properties, without elaborating the flavor compounds obtained by the MR. In this review, we have mainly introduced the Maillard flavor (MF), the main substances producing MF, and detection methods. Subsequently, the main influencing factors of MF, from the selection of materials (protein sources, enzymatic hydrolysis methods, molecular weights of peptides) to the reaction conditions (temperature, pH), are also described. In addition, the existing adverse effects of MR on the biological properties of protein were also pointed out.